(untitled) (College of Basic Education Research Journal, 2025)
The geography infection from the beginning in determining the emirate in Andalusia only for a month related to the economy in that period, including the geographical position of Andalusia, as Andalusia is located in a specific location between Europe and Africa, which helped to enhance the social movement, in addition to the geographical nature, as the diversity of gems (mountains, coasts, plains) contributed to providing natural and diverse things, which supports and growth, in addition to the impact of the climate from the climate, as it contributed to standing in the prosperity of agriculture, which increased self-sufficiency and securing food, as migrations and expansion were a prominent part. The geographical factor facilitated the movement of Arab and Islamic migrations to the h 138 region, which led to the Umayyad Emirate in 756/ AD.